FACTORS ASSOCIATED WITH HEALTH LITERACY ON BREAST CANCER BASED ON THE HEALTH BELIEF MODEL IN INDONESIA - Anggraini, Dian; Nurdina, Gina; Lindayani, Linlin; Noviyanti, Winia (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
Breast cancer is a leading cause of morbidity and mortality among women worldwide. Health literacy plays a pivotal role in early detection and prevention, particularly in low- and middle-income countries. This study aimed to identify factors associated with breast cancer health literacy using the Health Belief Model (HBM) framework. A cross-sectional study was conducted among 135 women aged 20–60 years in West Java, Indonesia. Variables included perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data were collected via validated questionnaires and analyzed using multiple linear regression. Results showed that self-efficacy and cues to action were the strongest predictors of health literacy (p < 0.05), while perceived barriers and susceptibility had weaker associations. These findings underscore the importance of enhancing confidence and providing tangible cues to improve breast cancer literacy among women.